Production method of rear floor boundary beam profile for automobile
By fine-tuning the composition of aluminum alloy and adjusting the production process parameters, the integrated molding method is used to produce rear floor edge beam profiles for automobiles, which solves the problems of poor uniformity of profile performance and degradation of mechanical properties in the existing technology, and achieves high performance, high precision and High stability profile production.
Patent Information
- Application Number
- CN202411790732.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-14
AI Technical Summary
The existing automotive rear floor edge beam profile production process relies on welding technology to reduce the performance of the profile material, and there are problems such as poor performance uniformity, mechanical properties, poor dimensional accuracy and low surface quality during integrated molding.
Using a production method including ingredients, casting, homogenization treatment, extrusion, quenching, stretching, cutting and aging treatment, by fine-tuning the alloy composition, strictly control the total content of Mn and Cr, and adjust the heating of the ingot and mold The temperature is adopted, and the progressive sinking bridge and step-type heating technology are used to improve moldability and dimensional accuracy, and reduce the formation of free-end coarse crystals.
It realizes high performance, high precision and high stability of the profile, avoids performance losses caused by welding, improves production efficiency and reduces production costs, and meets the needs of integrated, high performance and high precision for automotive aluminum profiles. .
Smart Images

Figure CN119426399A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum alloy extrusion, and specifically discloses a production method of a rear floor side beam profile for an automobile. Background Art
[0002] Al-Mg-Si aluminum alloys play an important role in many industries due to their excellent formability and comprehensive mechanical properties, especially in the field of automobile manufacturing, where they have become a key material for achieving vehicle lightweighting. The use of Al-Mg-Si aluminum alloys in vehicles not only helps to improve fuel efficiency, but also reduces emissions, which is in line with the current development trend of environmental protection and energy conservation. However, in the process of automobile manufacturing, most traditional aluminum alloy parts rely on welding technology for connection. This process often leads to a decrease in material properties due to the heat affected zone of welding, such as a decrease in strength and corrosion resistance. In addition, welding also increases production costs and time, limiting production efficiency. In order to overcome these problems, the industry has been seeking to reduce the welding process and instead develop large-scale components that can be manufactured through integrated molding technology. Integrated molding to manufacture large-scale components can reduce the number of material connection points, thereby reducing the performance loss caused by welding, while improving the stability and reliability of the overall structure. However, large-scale components often face problems such as poor performance uniformity, decreased mechanical properties, poor dimensional accuracy, and low surface quality when integrated molding. In view of the above problems, it is necessary to study and design a new production method for rear floor side beam profiles for automobiles to overcome the problems existing in the production of existing rear floor side beam profiles for automobiles. Summary of the invention
[0003] The present invention proposes a method for producing rear floor side beam profiles for automobiles to solve the problems faced in the production process of existing rear floor side beam profiles for automobiles, such as reliance on welding technology for connection leading to degradation of profile material performance, poor profile performance uniformity, degradation of mechanical properties, and poor dimensional accuracy.
[0004] The present invention provides a method for producing a rear floor side beam profile for an automobile, comprising the following steps:
[0005] S1. Ingredients: Prepare aluminum alloy raw materials according to the following weight ratios: Si: 0.65% to 0.70%, Fe: ≤0.25%, Cu: 0.11% to 0.16%, Mn: 0.25% to 0.30%, Mg: 0.55% to 0.60%, Zn: ≤0.10%, Cr: 0.15% to 0.20%, and the balance is Al;
[0006] S2. Casting: The aluminum alloy raw material prepared in step S1 is placed in a smelting furnace for casting to obtain a cast rod;
[0007] S3. Cast rod homogenization: homogenizing the cast rod obtained in step S2 to obtain a round ingot;
[0008] S4. Extrusion: placing the round ingot obtained in step S3 into an extrusion device for extrusion to obtain a profile, wherein the diverter slots on both sides of the feed port of the upper die of the extrusion die are progressive sinking bridges, and the round ingot is heated by a stepwise heating method, the heating temperature of the head end of the round ingot is 510°C to 530°C, the heating temperature of the tail end is 490°C to 510°C, the temperature of the extrusion barrel is 420°C to 460°C, the heating temperature of the extrusion die is 490°C to 510°C, and the product speed is 0.7m / min to 1.2m / min;
[0009] S5. Profile quenching, stretching and cutting: quenching the profile obtained in step S4, stretching it online after quenching, and cutting the stretched profile into a specified length;
[0010] S6. Aging treatment: The profile cut in step S5 is subjected to aging treatment at an aging temperature of 170°C to 180°C for 8 hours to obtain a rear floor side beam profile for automobiles.
[0011] According to a method for producing a rear floor side beam profile for an automobile in some embodiments of the present application, in step S1, the ingredients are Si: 0.65% to 0.70%, Fe: ≤0.17%, Cu: 0.12% to 0.14%, Mn: 0.27% to 0.30%, Mg: 0.55% to 0.58%, Zn: ≤0.01%, Cr: 0.15% to 0.17%, and the balance is Al.
[0012] According to a production method of a rear floor side beam profile for automobiles in some embodiments of the present application, in the step S2, during smelting, the smelting temperature is 730°C to 750°C, when molten aluminum appears in the smelting furnace, the electromagnetic stirrer of the smelting furnace is turned on, and the refining agent is pumped into the molten aluminum surface by argon gas, and the slag is removed by a slag removal vehicle after refining. After slag removal, the molten aluminum is allowed to stand for 15 minutes before casting, and before casting, pure aluminum chips are spread on the bottom of the crystallizer and molten aluminum is put into the crystallizer. When the aluminum chips are in a semi-solidified state, casting is started, and Al-Ti-B wire is added to the molten aluminum at the beginning of casting to perform grain refinement treatment. The casting temperature is 695°C to 715°C, the casting speed is 29mm / min, and the cooling water flow rate is 2.2m 3 / min. During casting, the aluminum liquid is degassed by three graphite rotor degassing technology, and the speed of each graphite rotor is controlled at 310r / min.
[0013] According to a method for producing a rear floor side beam profile for an automobile in some embodiments of the present application, in step S3, the temperature of the homogenization treatment is 560° C., and the time of the homogenization treatment is 6 hours.
[0014] According to a method for producing a rear floor side beam profile for an automobile in some embodiments of the present application, in step S3, the round ingot is a Φ582 mm round ingot.
[0015] According to a method for producing a rear floor side beam profile for an automobile in some embodiments of the present application, in step S4, the round ingot is subjected to a peeling treatment before extrusion, and the peeling treatment includes peeling by car skin or hot peeling by an online peeling machine. During extrusion, the ingot is extruded by a 12,500-ton extruder, and the extrusion ratio is 30.64.
[0016] According to a method for producing a rear floor side beam profile for an automobile in some embodiments of the present application, in step S4, the progressive sinking bridge of the extrusion die includes a plurality of stepped diverter bridges, each of which has a different depth and width.
[0017] According to a method for producing a rear floor side beam profile for an automobile in some embodiments of the present application, in the step S5, the quenching method is online water mist quenching.
[0018] According to a method for producing a rear floor side beam profile for an automobile in some embodiments of the present application, in step S5, the stretching amount in the online stretching is 0.5% to 1.5%.
[0019] According to a method for producing a rear floor side beam profile for an automobile in some embodiments of the present application, in step S6, the diameter of the circumscribed circle of the rear floor side beam profile for an automobile is 471 mm.
[0020] The present invention provides a production method for a rear floor side beam profile for automobiles. The method can fine-tune the alloy composition, strictly control the total content of Mn and Cr within the range of 0.40% to 0.50%, increase the recrystallization temperature, effectively inhibit the grain growth during the extrusion process, control the formation of coarse grains at the free end, and improve the alloy formability. The method can solve the problems of difficult control of dimensional accuracy and poor welding comprehensive performance of profiles with long cantilevers and large openings by adjusting the extrusion process parameters such as the ingot heating temperature and the mold temperature. The method can form large-size profiles in an integrated manner without multiple welding, thereby improving the overall mechanical properties of the profile, improving production efficiency, and reducing production costs. The method can optimize the diverter grooves on both sides of the upper mold inlet to achieve the 90° angle tolerance of GB / T 14846-2014 ultra-high precision grade makes the size tolerance of the two openings reach 0-0.5mm, which is higher than the national standard ultra-high precision grade tolerance requirement. After aging, the tensile strength, yield strength, elongation and exfoliation corrosion resistance of the profile can meet the standards, with excellent comprehensive performance, meeting the requirements of automotive aluminum profiles for integration, high performance and high precision. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1It is a schematic flow diagram of a method for producing a rear floor side beam profile for an automobile in the present invention;
[0022] Figure 2 This is a macroscopic grain structure detection diagram of the first portion of the cast rod in Example 3 of the present invention;
[0023] Figure 3 This is a low-magnification grain structure detection diagram of the second portion of the cast rod in Example 3 of the present invention;
[0024] Figure 4 This is a high-magnification microstructure test image of the rear floor side beam profile for automobiles in Example 3 of the present invention;
[0025] Figure 5 This is a graph showing the spalling corrosion detection of the rear floor side beam profile for an automobile in Example 3 of the present invention;
[0026] Figure 6 This is a macroscopic grain structure detection diagram of the first portion of the cast rod in Example 4 of the present invention;
[0027] Figure 7 This is a low-magnification grain structure detection diagram of the second portion of the cast rod in Example 4 of the present invention;
[0028] Figure 8 This is a high-magnification microstructure test image of the rear floor side beam profile for automobiles in Example 4 of the present invention;
[0029] Fig. 9 This is a graph showing the spalling corrosion detection of the rear floor side beam profile for automobiles in Example 4 of the present invention;
[0030] Fig.10 This is a macroscopic grain structure detection diagram of the first portion of the cast rod in Example 5 of the present invention;
[0031] Fig.11 This is a macroscopic grain structure detection diagram of the second portion of the cast rod in Example 5 of the present invention;
[0032] Fig.12 This is a high-magnification microstructure test image of the rear floor side beam profile for automobiles in Example 5 of the present invention;
[0033] Fig.13 This is a graph showing the spalling corrosion detection of the rear floor side beam profile for an automobile in Example 5 of the present invention.
[0034] Fig.14 This is a macroscopic grain structure detection diagram of the first portion of the cast rod in Example 6 of the present invention;
[0035] Fig.15 This is a macroscopic grain structure detection diagram of the second portion of the cast rod in Example 6 of the present invention;
[0036] Fig.16This is a high-magnification microstructure test image of the rear floor side beam profile for automobiles in Example 6 of the present invention;
[0037] Fig.17 This is a graph showing the spalling corrosion detection of the rear floor side beam profile for automobiles in Example 6 of the present invention;
[0038] Fig.18 This is a macroscopic grain structure detection diagram of the first portion of the cast rod in Example 7 of the present invention;
[0039] Fig.19 This is a macroscopic grain structure detection diagram of the second portion of the cast rod in Example 7 of the present invention;
[0040] Fig. 20 This is a high-magnification microstructure test image of the rear floor side beam profile for automobiles in Example 7 of the present invention;
[0041] Fig.21 This is a graph showing the spalling corrosion detection of the rear floor side beam profile for an automobile in Example 7 of the present invention;
[0042] Fig. 22 This is a macroscopic grain structure detection diagram of the first part of the cast rod in Comparative Example 1 of the present invention;
[0043] Fig.23 This is a low-magnification grain structure detection diagram of the second part of the cast rod in Comparative Example 1 of the present invention;
[0044] Fig.24 This is a high-magnification microstructure test image of the rear floor side beam profile for automobiles in Comparative Example 1 of the present invention;
[0045] Fig.25 This is a graph showing the peeling corrosion detection of the rear floor side beam profile for automobiles in Comparative Example 1 of the present invention;
[0046] Fig.26 This is a low-magnification grain structure detection diagram of the first part of the cast rod in Comparative Example 2 of the present invention;
[0047] Fig. 27 This is a low-magnification grain structure detection diagram of the second part of the cast rod in Comparative Example 2 of the present invention;
[0048] Fig.28 This is a high-magnification microstructure test image of the rear floor side beam profile for automobiles in Comparative Example 2 of the present invention;
[0049] Fig.29 This is a graph showing the spalling corrosion detection of the rear floor side beam profile for automobiles in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0050] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0051] Embodiment 1, this embodiment provides a method for producing a rear floor side beam profile for an automobile, such as Figure 1 As shown, the following steps are included:
[0052] S1. Ingredients: Prepare aluminum alloy raw materials according to the following weight ratios: Si: 0.65% to 0.70%, Fe: ≤0.25%, Cu: 0.11% to 0.16%, Mn: 0.25% to 0.30%, Mg: 0.55% to 0.60%, Zn: ≤0.10%, Cr: 0.15% to 0.20%, and the balance is Al;
[0053] S2. Casting: The aluminum alloy raw material prepared in step S1 is placed in a smelting furnace for casting to obtain a cast rod;
[0054] S3. Homogenization of cast rods: homogenizing the cast rods obtained in step S2 to obtain round ingots;
[0055] S4. Extrusion: placing the round ingot obtained in step S3 into an extrusion device for extrusion to obtain a profile, wherein the diverter grooves on both sides of the feed port of the upper die of the extrusion die are progressive sinking bridges to form a material storage cavity, which increases the material storage space, so that the aluminum alloy is reasonably distributed, the aluminum supply balance of the profile is ensured, the supply of the part away from the core is more sufficient, the formability and dimensional accuracy are improved, and the formation of coarse grains at the free end is reduced. The round ingot is heated by a step-by-step heating method, the heating temperature of the head end of the round ingot is 510°C to 530°C, the heating temperature of the tail end is 490°C to 510°C, the temperature of the extrusion barrel is 420°C to 460°C, the heating temperature of the extrusion die is 490°C to 510°C, and the product speed is 0.7m / min to 1.2m / min;
[0056] S5. Profile quenching, stretching and cutting: The profile obtained in step S4 is quenched, stretched online after quenching, and the stretched profile is cut into a specified length;
[0057] S6. Aging treatment: The profile cut in step S5 is subjected to aging treatment at an aging temperature of 170°C to 180°C for 8 hours to obtain a rear floor side beam profile for automobiles.
[0058] Embodiment 2: This embodiment provides a method for producing a rear floor side beam profile for an automobile, comprising the following steps:
[0059] S1. Ingredients: Aluminum alloy raw materials are prepared according to the following weight ratios: Si: 0.65% to 0.70%, Fe: ≤0.25%, Cu: 0.11% to 0.16%, Mn: 0.25% to 0.30%, Mg: 0.55% to 0.60%, Zn: ≤0.10%, Cr: 0.15% to 0.20%, and the balance is Al; In this embodiment, the total content of Mn and Cr is strictly controlled at 0.40% to 0.50% to increase the recrystallization temperature, reduce the recrystallization driving force, slow down the grain growth rate, and reduce the free end coarse grains. The main strengthening phase of the alloy is Mg2Si. In this embodiment, the excess Si is designed to refine the Mg2Si strengthening phase, and at the same time, Si is used to form Al with Al after precipitation. 3.2 1Si 0.47 phase, further improve the mechanical properties, preferably, the ingredients can be: Si: 0.65% to 0.70%, Fe: ≤0.17%, Cu: 0.12% to 0.14%, Mn: 0.27% to 0.30%, Mg: 0.55% to 0.58%, Zn: ≤0.01%, Cr: 0.15% to 0.17%, and the balance is Al. ;
[0060] S2. Casting: The aluminum alloy raw material prepared in step S1 is placed in a smelting furnace for casting to obtain a cast rod;
[0061] As a preferred embodiment of this embodiment, specifically, during casting, the smelting temperature is 730℃~750℃. When aluminum liquid appears in the smelting furnace, the electromagnetic stirrer of the smelting furnace is turned on to make the molten alloy elements more evenly distributed. The refining agent is driven into the aluminum liquid surface by argon gas. After refining, the slag is removed by a slag removal vehicle. After the slag removal, the aluminum liquid is left to stand for 15 minutes before casting. In order to prevent cracks from forming at the bottom of the large-diameter cast rod during casting, pure aluminum chips are spread on the bottom of the crystallizer before casting and aluminum liquid is placed into the crystallizer. Casting begins when the aluminum chips are in a semi-solidified state. The surface quality of the cast rod obtained by this technology is good, and the generation of bottom cracks is effectively controlled. At the beginning of casting, Al-Ti-B wire is added to the aluminum liquid for grain refinement. Preferably, Al-Ti-B wire can be added to the aluminum liquid through a wire feeding device. The casting temperature is 695℃~715℃, the casting speed is 29mm / min, and the cooling water flow rate is 2.2m 3 / min, during casting, the aluminum liquid is degassed by three graphite rotors to reduce the hydrogen content in the aluminum liquid. The speed of each graphite rotor is controlled at 310r / min;
[0062] S3. Homogenization of cast rods: The cast rods obtained in step S2 are homogenized to obtain round ingots, which may be Φ582 mm round ingots;
[0063] As a preferred embodiment of this invention, specifically, the temperature of the homogenization treatment is 560° C., and the time of the homogenization treatment is 6 hours;
[0064] S4. Extrusion: putting the round ingot obtained in step S3 into an extrusion device for extrusion to obtain a profile, wherein the diverter grooves on both sides of the feed port of the upper die of the extrusion die are progressive sinking bridges, and the progressive sinking bridges include a plurality of stepped diverter bridges, each of which has a different depth and width, forming a material holding cavity, increasing the material holding space, making the feeding of the part away from the core more sufficient, improving the formability and dimensional accuracy, reducing the formation of coarse grains at the free end, heating the round ingot by a stepped heating method, increasing the head end temperature to ensure the quenching temperature, and improving the mechanical properties, the heating temperature of the head end of the round ingot is 510℃~530℃, the heating temperature of the tail is 490℃~510℃, the temperature of the extrusion barrel is 420℃~460℃, the heating temperature of the extrusion die is 490℃~510℃, and the product speed is 0.7m / min~1.2m / min;
[0065] As a preferred embodiment of the present invention, specifically, the length of the round ingot can be 1680 mm. The round ingot is subjected to a peeling treatment before extrusion to avoid impurities such as the surface oxide layer from causing shrinkage defects. The peeling treatment includes peeling by car skin or hot peeling by an online peeling machine. During extrusion, the round ingot is extruded by a 12,500-ton extruder, and the extrusion ratio is 30.64.
[0066] S5. Profile quenching, stretching and cutting: The profile obtained in step S4 is quenched, stretched online after quenching, and the stretched profile is cut into a specified length;
[0067] As a preferred embodiment of the present invention, specifically, the quenching method of quenching is online water mist quenching, and the stretching amount in the online stretching is 0.5% to 1.5%;
[0068] S6 aging treatment: The profile cut in step S5 was subjected to aging treatment, the aging temperature was 170 ℃ ~ 180 ℃, the aging time was 8h, and the rear floor side beam profile for automobiles was obtained;
[0069] As a preferred embodiment of the present invention, specifically, the circumscribed circle diameter of the rear floor side beam profile for automobiles is 471 mm, and the cross-sectional area can be 125.21 cm 2 .
[0070] Embodiment 3, this embodiment provides a method for producing a rear floor side beam profile for automobiles, the purpose of which is to produce a rear floor side beam profile for automobiles with an outer circle of 471mm, an outer contour size and an outer wall thickness size reaching the ultra-high precision level of GB / T 14846-2008, wherein the cantilever right angle tolerance reaches ±0.5°, the opening size tolerance is 0-0.5mm; the yield strength is ≥200MPa, the tensile strength is ≥250MPa, and the elongation after fracture is A 50≥6%; Brinell hardness ≥85HBW; coarse grain layer ≤2.5mm; exfoliation corrosion ≥EA level, with high comprehensive performance automotive rear floor side beam profile. Specifically includes the following steps:
[0071] S1. Ingredients: Prepare aluminum alloy raw materials according to the following weight ratio: Si: 0.70%, Fe: 0.20%, Cu: 0.16%, Mn: 0.30%, Mg: 0.60%, Cr: 0.20%, Zn: 0.10%, and the balance is Al;
[0072] S2. Melting and casting: the aluminum alloy raw material prepared in step S1 is placed in a smelting furnace for melting and casting to obtain cast rods. During melting and casting, the melting temperature is 750°C, the refining temperature is 735°C, the refining agent dosage is 2.2kg / TAl, and waste materials are not allowed to be added. When aluminum liquid appears in the smelting furnace, the electromagnetic stirrer of the smelting furnace is turned on to make the molten alloy elements more evenly distributed. The refining agent is pumped into the aluminum liquid surface by argon gas. After refining, the slag is removed by a slag removal vehicle. After the slag is removed, the aluminum liquid is allowed to stand for 15 minutes before casting. In order to prevent cracks from occurring at the bottom of large-diameter cast rods during casting, pure aluminum chips are spread on the bottom of the crystallizer before casting and aluminum liquid is placed into the crystallizer. Casting begins when the aluminum chips are in a semi-solidified state. The cast rods obtained using this technology have good surface quality and effectively control the occurrence of bottom cracks. At the beginning of casting, Al-Ti-B wire is added to the aluminum liquid for grain refinement. Al-Ti-B wire can be added to the aluminum liquid through wire feeding equipment. The casting temperature is 710℃, the casting speed is 29mm / min, and the cooling water flow rate is 2.2m 3 / min, during casting, the aluminum liquid is degassed by three graphite rotor degassing technology to reduce the hydrogen content in the aluminum liquid. The speed of each graphite rotor is controlled at 310r / min, the diameter of the cast rod is 582mm, and the slag content of the cast rod must meet the secondary requirements of GB / T32186-2015; the macrostructure of the cast rod is tested, and the macrograin structure of the cast rod meets the grain size level 1 and is qualified. The macrograin detection diagrams of the first and second parts of the cast rod are shown as follows Figure 2 and Figure 3 As shown;
[0073] S3. Homogenization of cast rods: The cast rods obtained in step S2 are homogenized to obtain round ingots, which may be round ingots of Φ582 mm, and the homogenization temperature is 560 ° C, and the homogenization time is 6 h;
[0074] S4 extrusion: the round ingot obtained in step S3 is placed in an extrusion device for extrusion to obtain a profile, extruded by a 12500 ton extruder, the round ingot length is 1680 mm, the round ingot car, the round ingot head heating temperature is 530 ° C, the tail heating temperature is 510 ° C, the extrusion die heating temperature is 500 ° C, the extrusion barrel heating temperature is 450 ° C, the product speed is 0.9 m / min;
[0075] S5. Profile quenching, stretching and cutting: The profile obtained in step S4 is quenched by online water mist quenching, and after quenching, it is stretched online with a stretching amount of 1%, and the stretched profile is cut into a specified length;
[0076] S6. Aging treatment: The profile cut in step S5 is subjected to aging treatment at an aging temperature of 175° C. for an aging time of 8 h to obtain a rear floor side beam profile for an automobile.
[0077] Dimension accuracy at key positions: Three pieces were randomly selected from the produced rear floor side beam profiles for automobiles, numbered and measured. The results of the key position dimension detection are shown in Table 1.
[0078] Table 1 Key dimension detection results
[0079]
[0080] Macrostructure: alkaline corrosive solution is used; test standard: GB / T6892-2015 General industrial aluminum and aluminum alloy extrusion profiles; test method: GB / T3246.2-2012 Deformed aluminum and aluminum alloy product structure test method Part 2: Macrostructure test method. Three pieces were randomly selected from the produced rear floor side beam profiles for automobiles, numbered and tested, and the macrostructure test results are shown in Table 2.
[0081] Table 2 Low-magnification tissue detection results
[0082]
[0083] High-magnification structure: Test equipment: AXIO universal research-grade inverted material microscope; Test standard: GB / T6892-2015 General industrial aluminum and aluminum alloy extrusion profiles; Test method: GB / T3246.1-2012 Deformed aluminum and aluminum alloy product structure inspection method Part 1: Microstructure inspection method. One piece was randomly selected from the produced automotive rear floor side beam profiles and numbered and inspected. The high-magnification metallographic structure inspection results are shown in Table 3. The high-magnification structure inspection diagram is shown in Table 3. Figure 4 shown.
[0084] Table 3 High magnification metallographic structure test results
[0085]
[0086] Mechanical properties and Brinell hardness: Testing equipment AG-X 100KN electronic universal testing machine, OMNITEST multifunctional hardness tester; Testing methods GB / T16865-2013 Specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products, GB / T231.1-2018 Brinell hardness test of metallic materials Part 1: Test method; Judgment criteria: tensile strength ≥ 250MPa, yield strength ≥ 200MPa, elongation after fracture A 50 mm≥6%, Brinell hardness≥85HBW. Three pieces were randomly selected from the produced rear floor side beam profiles for automobiles, numbered and tested. The mechanical properties test results are shown in Table 4.
[0087] Table 4 Mechanical properties test results
[0088]
[0089] Exfoliation corrosion: Test equipment: digital constant temperature water bath crucible; Test standard: GB / T22639-2008 Exfoliation corrosion test method for aluminum alloy processed products; 3 pieces were randomly selected from the produced rear floor side beam profiles for automobiles and numbered and tested. The exfoliation corrosion test results are shown in Table 5. Figure 5 shown.
[0090] Table 5 Exfoliation corrosion test results
[0091]
[0092] Embodiment 4, this embodiment provides a method for producing a rear floor side beam profile for automobiles, the purpose of which is to produce a rear floor side beam profile for automobiles with an outer circle of 471mm, an outer contour size and an outer wall thickness size reaching the ultra-high precision level of GB / T 14846-2008, wherein the cantilever right angle tolerance reaches ±0.5°, the opening size tolerance is 0-0.5mm; the yield strength is ≥200MPa, the tensile strength is ≥250MPa, and the elongation after fracture is A 50 ≥6%; Brinell hardness ≥85HBW; coarse grain layer ≤2.5mm; exfoliation corrosion ≥EA level, with high comprehensive performance automotive rear floor side beam profile. Specifically includes the following steps:
[0093] S1. Ingredients: Prepare aluminum alloy raw materials according to the following weight ratio: Si: 0.65%, Fe: 0.18%, Cu: 0.11%, Mn: 0.25%, Mg: 0.55%, Cr: 0.15%, Zn: 0.05%, and the balance is Al;
[0094] S2. Melting and casting: the aluminum alloy raw material prepared in step S1 is placed in a smelting furnace for melting and casting to obtain cast rods. During melting and casting, the melting temperature is 740°C, the refining temperature is 735°C, the refining agent dosage is 2.2kg / TAl, and waste materials are not allowed to be added. When molten aluminum appears in the smelting furnace, the electromagnetic stirrer of the smelting furnace is turned on to make the molten alloy elements more evenly distributed. The refining agent is pumped into the surface of the molten aluminum by argon gas. After refining, the slag is removed by a slag removal vehicle. After slag removal, the molten aluminum is allowed to stand for 15 minutes before casting. In order to prevent cracks from occurring at the bottom of large-diameter cast rods during casting, pure aluminum chips are spread on the bottom of the crystallizer before casting and molten aluminum is placed into the crystallizer. Casting begins when the aluminum chips are in a semi-solidified state. The cast rods obtained using this technology have good surface quality and effectively control the occurrence of bottom cracks. At the beginning of casting, Al-Ti-B wire is added to the aluminum liquid for grain refinement. Al-Ti-B wire can be added to the aluminum liquid through wire feeding equipment. The casting temperature is 700℃, the casting speed is 29mm / min, and the cooling water flow rate is 2.2m 3 / min, during casting, the aluminum liquid is degassed by three graphite rotor degassing technology to reduce the hydrogen content in the aluminum liquid. The speed of each graphite rotor is controlled at 310r / min, the diameter of the cast rod is 582mm, and the slag content of the cast rod must meet the secondary requirements of GB / T32186-2015; the macrostructure of the cast rod is tested, and the macrograin structure of the cast rod meets the grain size level 1 and is qualified. The macrograin detection diagrams of the first and second parts of the cast rod are shown as follows Figure 6 and Figure 7 As shown;
[0095] S3. Homogenization of cast rods: The cast rods obtained in step S2 are homogenized to obtain round ingots, which may be round ingots of Φ582 mm, and the homogenization temperature is 560 ° C, and the homogenization time is 6 h;
[0096] S4 extrusion: the round ingot obtained in step S3 is placed in an extrusion device for extrusion to obtain a profile, using a 12500 ton extruder for extrusion, the round ingot length is 1680mm, the round ingot car, the round ingot head heating temperature is 520 ° C, the tail heating temperature is 500 ° C, the extrusion die heating temperature is 500 ° C, the extrusion barrel heating temperature is 460 ° C, the product speed is 1.1m / min;
[0097] S5. Profile quenching, stretching and cutting: The profile obtained in step S4 is quenched by online water mist quenching, and after quenching, it is stretched online with a stretching amount of 1%, and the stretched profile is cut into a specified length;
[0098] S6. Aging treatment: The profile cut in step S5 is subjected to aging treatment at an aging temperature of 175° C. for an aging time of 8 h to obtain a rear floor side beam profile for an automobile.
[0099] Dimension accuracy at key positions: Three pieces were randomly selected from the produced rear floor side beam profiles for automobiles, numbered and measured. The results of the key position dimension detection are shown in Table 6.
[0100] Table 6 Key dimension detection results
[0101]
[0102]
[0103] Macrostructure: alkaline corrosive solution is used; test standard: GB / T6892-2015 General industrial aluminum and aluminum alloy extrusion profiles; test method: GB / T3246.2-2012 Deformed aluminum and aluminum alloy product structure test method Part 2: Macrostructure test method. Three pieces were randomly selected from the produced rear floor side beam profiles for automobiles, numbered and tested, and the macrostructure test results are shown in Table 7.
[0104] Table 7 Low-magnification tissue detection results
[0105]
[0106] High-magnification structure: Test equipment: AXIO universal research-grade inverted material microscope; Test standard: GB / T6892-2015 General industrial aluminum and aluminum alloy extrusion profiles; Test method: GB / T3246.1-2012 Deformed aluminum and aluminum alloy product structure inspection method Part 1: Microstructure inspection method. One piece was randomly selected from the produced rear floor side beam profile for automobiles and numbered and inspected. The high-magnification metallographic structure inspection results are shown in Table 8. The high-magnification structure inspection diagram is shown in Table 8. Figure 8 shown.
[0107] Table 8 High magnification metallographic structure test results
[0108]
[0109] Mechanical properties and Brinell hardness: Testing equipment AG-X 100KN electronic universal testing machine, OMNITEST multifunctional hardness tester; Testing methods GB / T16865-2013 Specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products, GB / T231.1-2018 Brinell hardness test of metallic materials Part 1: Test method; Judgment criteria: tensile strength ≥ 250MPa, yield strength ≥ 200MPa, elongation after fracture A 50 mm≥6%, Brinell hardness≥85HBW. Three pieces were randomly selected from the produced rear floor side beam profiles for automobiles, numbered and tested. The mechanical properties test results are shown in Table 9.
[0110] Table 9 Mechanical properties test results
[0111]
[0112] Exfoliation corrosion: Test equipment: digital constant temperature water bath crucible; Test standard: GB / T22639-2008 Exfoliation corrosion test method for aluminum alloy processed products; 3 pieces were randomly selected from the produced rear floor side beam profiles for automobiles and numbered and tested. The exfoliation corrosion test results are shown in Table 10. Fig. 9 shown.
[0113] Table 10 Exfoliation corrosion test results
[0114]
[0115] Embodiment 5, this embodiment provides a method for producing a rear floor side beam profile for automobiles, the purpose of which is to produce a rear floor side beam profile for automobiles with an outer circle of 471mm, an outer contour size and an outer wall thickness size reaching the ultra-high precision level of GB / T 14846-2008, wherein the cantilever right angle tolerance reaches ±0.5°, the opening size tolerance is 0-0.5mm; the yield strength is ≥200MPa, the tensile strength is ≥250MPa, and the elongation after fracture is A 50 ≥6%; Brinell hardness ≥85HBW; coarse grain layer ≤2.5mm; exfoliation corrosion ≥EA level, with high comprehensive performance automotive rear floor side beam profile. Specifically includes the following steps:
[0116] S1. Ingredients: Prepare aluminum alloy raw materials according to the following weight ratio: Si: 0.65%, Fe: 0.17%, Cu: 0.13%, Mn: 0.29%, Mg: 0.57%, Cr: 0.15%, Zn: 0.01%, and the balance is Al;
[0117] S2. Melting and casting: the aluminum alloy raw material prepared in step S1 is placed in a smelting furnace for melting and casting to obtain cast rods. During melting and casting, the melting temperature is 740°C, the refining temperature is 735°C, the refining agent dosage is 2.2kg / TAl, and waste materials are not allowed to be added. When molten aluminum appears in the smelting furnace, the electromagnetic stirrer of the smelting furnace is turned on to make the molten alloy elements more evenly distributed. The refining agent is pumped into the surface of the molten aluminum by argon gas. After refining, the slag is removed by a slag removal vehicle. After slag removal, the molten aluminum is allowed to stand for 15 minutes before casting. In order to prevent cracks from occurring at the bottom of large-diameter cast rods during casting, pure aluminum chips are spread on the bottom of the crystallizer before casting and molten aluminum is placed into the crystallizer. Casting begins when the aluminum chips are in a semi-solidified state. The cast rods obtained using this technology have good surface quality and effectively control the occurrence of bottom cracks. At the beginning of casting, Al-Ti-B wire is added to the aluminum liquid for grain refinement. Al-Ti-B wire can be added to the aluminum liquid through wire feeding equipment. The casting temperature is 705℃, the casting speed is 29mm / min, and the cooling water flow rate is 2.2m 3 / min, during casting, the aluminum liquid is degassed by three graphite rotor degassing technology to reduce the hydrogen content in the aluminum liquid. The speed of each graphite rotor is controlled at 310r / min, the diameter of the cast rod is 582mm, and the slag content of the cast rod must meet the secondary requirements of GB / T32186-2015; the macrostructure of the cast rod is tested, and the macrograin structure of the cast rod meets the grain size level 1 and is qualified. The macrograin detection diagrams of the first and second parts of the cast rod are shown as follows Fig.10 and Fig.11 As shown;
[0118] S3. Homogenization of cast rods: The cast rods obtained in step S2 are homogenized to obtain round ingots, which may be round ingots of Φ582 mm, and the homogenization temperature is 560 ° C, and the homogenization time is 6 h;
[0119] S4 extrusion: the round ingot obtained in step S3 is placed in an extrusion device for extrusion to obtain a profile, using a 12500 ton extruder for extrusion, the round ingot length is 1680mm, the round ingot car, the round ingot head heating temperature is 520 ° C, the tail heating temperature is 510 ° C, the extrusion die heating temperature is 500 ° C, the extrusion barrel heating temperature is 440 ° C, the product speed is 1m / min;
[0120] S5. Profile quenching, stretching and cutting: The profile obtained in step S4 is quenched by online water mist quenching, and after quenching, it is stretched online with a stretching amount of 1%, and the stretched profile is cut into a specified length;
[0121] S6. Aging treatment: The profile cut in step S5 is subjected to aging treatment at an aging temperature of 175° C. for an aging time of 8 h to obtain a rear floor side beam profile for an automobile.
[0122] Dimension accuracy at key positions: Three pieces were randomly selected from the produced rear floor side beam profiles for automobiles, numbered and measured. The results of the key position dimension detection are shown in Table 11.
[0123] Table 11 Key dimension detection results
[0124]
[0125] Macrostructure: alkaline corrosive solution is used; test standard: GB / T6892-2015 General industrial aluminum and aluminum alloy extrusion profiles; test method: GB / T3246.2-2012 Deformed aluminum and aluminum alloy product microstructure test method Part 2: Macrostructure test method. Three pieces were randomly selected from the produced automotive rear floor side beam profiles and numbered and tested. The macrostructure test results are shown in Table 12.
[0126] Table 12 Low-power tissue detection results
[0127]
[0128] High-magnification structure: Test equipment: AXIO universal research-grade inverted material microscope; Test standard: GB / T6892-2015 General industrial aluminum and aluminum alloy extrusion profiles; Test method: GB / T3246.1-2012 Deformed aluminum and aluminum alloy product structure inspection method Part 1: Microstructure inspection method. One piece was randomly selected from the produced rear floor side beam profile for automobiles and numbered and inspected. The high-magnification metallographic structure inspection results are shown in Table 13. The high-magnification structure inspection diagram is shown in Table 13. Fig.12 shown.
[0129] Table 13 High magnification metallographic structure test results
[0130]
[0131]
[0132] Mechanical properties and Brinell hardness: Testing equipment AG-X 100KN electronic universal testing machine, OMNITEST multifunctional hardness tester; Testing methods GB / T16865-2013 Specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products, GB / T231.1-2018 Brinell hardness test of metallic materials Part 1: Test method; Judgment criteria: tensile strength ≥250MPa, yield strength ≥200MPa, elongation after fracture A 50 mm≥6%, Brinell hardness≥85HBW. Three pieces were randomly selected from the produced rear floor side beam profiles for automobiles, numbered and tested. The mechanical properties test results are shown in Table 14.
[0133] Table 14 Mechanical properties test results
[0134]
[0135] Exfoliation corrosion: Test equipment: digital constant temperature water bath crucible; Test standard: GB / T22639-2008 Exfoliation corrosion test method for aluminum alloy processed products; 3 pieces were randomly selected from the produced rear floor side beam profiles for automobiles and numbered and tested. The exfoliation corrosion test results are shown in Table 15. Fig.13 shown.
[0136] Table 15 Exfoliation corrosion test results
[0137]
[0138] Embodiment 6, this embodiment provides a method for producing a rear floor side beam profile for automobiles, the purpose of which is to produce a rear floor side beam profile for automobiles with an outer circle of 471mm, an outer contour size and an outer wall thickness size reaching the ultra-high precision level of GB / T 14846-2008, wherein the cantilever right angle tolerance reaches ±0.5°, the opening size tolerance is 0-0.5mm; the yield strength is ≥200MPa, the tensile strength is ≥250MPa, and the elongation after fracture is A 50 ≥6%; Brinell hardness ≥85HBW; coarse grain layer ≤2.5mm; exfoliation corrosion ≥EA level, with high comprehensive performance automotive rear floor side beam profile. Specifically includes the following steps:
[0139] S1. Ingredients: Prepare aluminum alloy raw materials according to the following weight ratio: Si: 0.70%, Fe: 0.17%, Cu: 0.14%, Mn: 0.30%, Mg: 0.58%, Cr: 0.17%, Zn: 0.01%, and the balance is Al;
[0140] S2. Melting and casting: the aluminum alloy raw material prepared in step S1 is placed in a smelting furnace for melting and casting to obtain cast rods. During melting and casting, the melting temperature is 740°C, the refining temperature is 735°C, the refining agent dosage is 2.2kg / TAl, and waste materials are not allowed to be added. When molten aluminum appears in the smelting furnace, the electromagnetic stirrer of the smelting furnace is turned on to make the molten alloy elements more evenly distributed. The refining agent is pumped into the surface of the molten aluminum by argon gas. After refining, the slag is removed by a slag removal vehicle. After slag removal, the molten aluminum is allowed to stand for 15 minutes before casting. In order to prevent cracks from occurring at the bottom of large-diameter cast rods during casting, pure aluminum chips are spread on the bottom of the crystallizer before casting and molten aluminum is placed into the crystallizer. Casting begins when the aluminum chips are in a semi-solidified state. The cast rods obtained using this technology have good surface quality and effectively control the occurrence of bottom cracks. At the beginning of casting, Al-Ti-B wire is added to the aluminum liquid for grain refinement. Al-Ti-B wire can be added to the aluminum liquid through wire feeding equipment. The casting temperature is 705℃, the casting speed is 29mm / min, and the cooling water flow rate is 2.2m 3 / min, during casting, the aluminum liquid is degassed by three graphite rotor degassing technology to reduce the hydrogen content in the aluminum liquid. The speed of each graphite rotor is controlled at 310r / min, the diameter of the cast rod is 582mm, and the slag content of the cast rod must meet the secondary requirements of GB / T32186-2015; the macrostructure of the cast rod is tested, and the macrograin structure of the cast rod meets the grain size level 1 and is qualified. The macrograin detection diagrams of the first and second parts of the cast rod are shown as follows Fig.14 and Fig.15 As shown;
[0141] S3. Homogenization of cast rods: The cast rods obtained in step S2 are homogenized to obtain round ingots, which may be round ingots of Φ582 mm, and the homogenization temperature is 560 ° C, and the homogenization time is 6 h;
[0142] S4 extrusion: the round ingot obtained in step S3 is placed in an extrusion device for extrusion to obtain a profile, using a 12500 ton extruder for extrusion, the round ingot length is 1680mm, the round ingot car, the round ingot head heating temperature is 520 ° C, the tail heating temperature is 510 ° C, the extrusion die heating temperature is 500 ° C, the extrusion barrel heating temperature is 440 ° C, the product speed is 1m / min;
[0143] S5. Profile quenching, stretching and cutting: The profile obtained in step S4 is quenched by online water mist quenching, and after quenching, it is stretched online with a stretching amount of 1%, and the stretched profile is cut into a specified length;
[0144] S6. Aging treatment: The profile cut in step S5 is subjected to aging treatment at an aging temperature of 175° C. for an aging time of 8 h to obtain a rear floor side beam profile for an automobile.
[0145] Dimension accuracy at key positions: Three pieces are randomly selected from the produced rear floor side beam profiles for automobiles, numbered and measured. The results of the key position dimension detection are shown in Table 16.
[0146] Table 16 Key dimension detection results
[0147]
[0148] Macrostructure: alkaline corrosive solution is used; test standard: GB / T6892-2015 General industrial aluminum and aluminum alloy extrusion profiles; test method: GB / T3246.2-2012 Deformed aluminum and aluminum alloy product microstructure test method Part 2: Macrostructure test method. Three pieces were randomly selected from the produced automotive rear floor side beam profiles and numbered and tested. The macrostructure test results are shown in Table 17.
[0149] Table 17 Low-power tissue detection results
[0150]
[0151] High-magnification structure: Test equipment: AXIO universal research-grade inverted material microscope; Test standard: GB / T6892-2015 General industrial aluminum and aluminum alloy extrusion profiles; Test method: GB / T3246.1-2012 Deformed aluminum and aluminum alloy product structure inspection method Part 1: Microstructure inspection method. One piece was randomly selected from the produced rear floor side beam profile for automobiles and numbered and inspected. The high-magnification metallographic structure inspection results are shown in Table 18. The high-magnification structure inspection diagram is shown in Table 18. Fig.16 shown.
[0152] Table 18 High magnification metallographic structure test results
[0153]
[0154] Mechanical properties and Brinell hardness: Testing equipment AG-X 100KN electronic universal testing machine, OMNITEST multifunctional hardness tester; Testing methods GB / T16865-2013 Specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products, GB / T231.1-2018 Brinell hardness test of metallic materials Part 1: Test method; Judgment criteria: tensile strength ≥250MPa, yield strength ≥200MPa, elongation after fracture A 50 mm≥6%, Brinell hardness≥85HBW. Three pieces were randomly selected from the produced rear floor side beam profiles for automobiles, numbered and tested. The mechanical properties test results are shown in Table 19.
[0155] Table 19 Mechanical properties test results
[0156]
[0157] Exfoliation corrosion: Test equipment: digital constant temperature water bath crucible; Test standard: GB / T22639-2008 Exfoliation corrosion test method for aluminum alloy processed products; 3 pieces were randomly selected from the produced rear floor side beam profiles for automobiles and numbered and tested. The exfoliation corrosion test results are shown in Table 20. Fig.17 shown.
[0158] Table 20 Exfoliation corrosion test results
[0159]
[0160] Embodiment 7, this embodiment provides a method for producing a rear floor side beam profile for automobiles, the purpose of which is to produce a rear floor side beam profile for automobiles with an outer circle of 471mm, an outer contour size and an outer wall thickness size reaching the ultra-high precision level of GB / T 14846-2008, wherein the cantilever right angle tolerance reaches ±0.5°, the opening size tolerance is 0-0.5mm; the yield strength is ≥200MPa, the tensile strength is ≥250MPa, and the elongation after fracture is A 50 ≥6%; Brinell hardness ≥85HBW; coarse grain layer ≤2.5mm; exfoliation corrosion ≥EA level, with high comprehensive performance automotive rear floor side beam profile. Specifically includes the following steps:
[0161] S1. Ingredients: Prepare aluminum alloy raw materials according to the following weight ratio: Si: 0.65%, Fe: 0.17%, Cu: 0.12%, Mn: 0.27%, Mg: 0.55%, Cr: 0.15%, Zn: 0.01%, and the balance is Al;
[0162] S2. Melting and casting: the aluminum alloy raw material prepared in step S1 is placed in a smelting furnace for melting and casting to obtain cast rods. During melting and casting, the melting temperature is 740°C, the refining temperature is 735°C, the refining agent dosage is 2.2kg / TAl, and waste materials are not allowed to be added. When molten aluminum appears in the smelting furnace, the electromagnetic stirrer of the smelting furnace is turned on to make the molten alloy elements more evenly distributed. The refining agent is pumped into the surface of the molten aluminum by argon gas. After refining, the slag is removed by a slag removal vehicle. After slag removal, the molten aluminum is allowed to stand for 15 minutes before casting. In order to prevent cracks from occurring at the bottom of large-diameter cast rods during casting, pure aluminum chips are spread on the bottom of the crystallizer before casting and molten aluminum is placed into the crystallizer. Casting begins when the aluminum chips are in a semi-solidified state. The cast rods obtained using this technology have good surface quality and effectively control the occurrence of bottom cracks. At the beginning of casting, Al-Ti-B wire is added to the aluminum liquid for grain refinement. Al-Ti-B wire can be added to the aluminum liquid through wire feeding equipment. The casting temperature is 705℃, the casting speed is 29mm / min, and the cooling water flow rate is 2.2m 3 / min, during casting, the aluminum liquid is degassed by three graphite rotor degassing technology to reduce the hydrogen content in the aluminum liquid. The speed of each graphite rotor is controlled at 310r / min, the diameter of the cast rod is 582mm, and the slag content of the cast rod must meet the secondary requirements of GB / T32186-2015; the macrostructure of the cast rod is tested, and the macrograin structure of the cast rod meets the grain size level 1 and is qualified. The macrograin detection diagrams of the first and second parts of the cast rod are shown as follows Fig.18 and Fig.19 As shown;
[0163] S3. Homogenization of cast rods: The cast rods obtained in step S2 are homogenized to obtain round ingots, which may be round ingots of Φ582 mm, and the homogenization temperature is 560 ° C, and the homogenization time is 6 h;
[0164] S4 extrusion: the round ingot obtained in step S3 is placed in an extrusion device for extrusion to obtain a profile, using a 12500 ton extruder for extrusion, the round ingot length is 1680mm, the round ingot car, the round ingot head heating temperature is 520 ° C, the tail heating temperature is 510 ° C, the extrusion die heating temperature is 500 ° C, the extrusion barrel heating temperature is 440 ° C, the product speed is 1m / min;
[0165] S5. Profile quenching, stretching and cutting: The profile obtained in step S4 is quenched by online water mist quenching, and after quenching, it is stretched online with a stretching amount of 1%, and the stretched profile is cut into a specified length;
[0166] S6. Aging treatment: The profile cut in step S5 is subjected to aging treatment at an aging temperature of 175° C. for an aging time of 8 h to obtain a rear floor side beam profile for an automobile.
[0167] Dimension accuracy at key positions: Three pieces are randomly selected from the produced rear floor side beam profiles for automobiles, numbered and measured. The results of the key position dimension detection are shown in Table 21.
[0168] Table 21 Key dimension detection results
[0169]
[0170] Macrostructure: alkaline corrosive solution is used; test standard: GB / T6892-2015 General industrial aluminum and aluminum alloy extrusion profiles; test method: GB / T3246.2-2012 Deformed aluminum and aluminum alloy product microstructure test method Part 2: Macrostructure test method. Three pieces were randomly selected from the produced rear floor side beam profiles for automobiles, numbered and tested, and the macrostructure test results are shown in Table 22.
[0171] Table 22 Low-power tissue detection results
[0172]
[0173] High-magnification structure: Test equipment: AXIO universal research-grade inverted material microscope; Test standard: GB / T6892-2015 General industrial aluminum and aluminum alloy extrusion profiles; Test method: GB / T3246.1-2012 Deformed aluminum and aluminum alloy product structure inspection method Part 1: Microstructure inspection method. One piece was randomly selected from the produced rear floor side beam profile for automobiles and numbered and inspected. The high-magnification metallographic structure inspection results are shown in Table 23. The high-magnification structure inspection diagram is shown in Table 23. Fig. 20 shown.
[0174] Table 23 High magnification metallographic structure test results
[0175]
[0176] Mechanical properties and Brinell hardness: Testing equipment AG-X 100KN electronic universal testing machine, OMNITEST multifunctional hardness tester; Testing methods GB / T16865-2013 Specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products, GB / T231.1-2018 Brinell hardness test of metallic materials Part 1: Test method; Judgment criteria: tensile strength ≥250MPa, yield strength ≥200MPa, elongation after fracture A 50 mm≥6%, Brinell hardness≥85HBW. Three pieces were randomly selected from the produced rear floor side beam profiles for automobiles, numbered and tested. The mechanical properties test results are shown in Table 24.
[0177] Table 24 Mechanical properties test results
[0178]
[0179] Exfoliation corrosion: Test equipment: digital constant temperature water bath crucible; Test standard: GB / T22639-2008 Exfoliation corrosion test method for aluminum alloy processed products; 3 pieces were randomly selected from the produced rear floor side beam profiles for automobiles and numbered and tested. The exfoliation corrosion test results are shown in Table 25. Fig.21 shown.
[0180] Table 25 Exfoliation corrosion test results
[0181]
[0182] Comparative Example 1: This comparative example provides a method for producing a rear floor side beam profile for an automobile, the purpose of which is to produce a rear floor side beam profile for an automobile with an outer circle of 471 mm, an outer contour dimension and an outer wall thickness dimension reaching the ultra-high precision level of GB / T 14846-2008, wherein the cantilever right angle tolerance reaches ±0.5°, the opening dimension tolerance is 0-0.5mm; the yield strength is ≥200MPa, the tensile strength is ≥250MPa, and the elongation after fracture is A 50 ≥6%; Brinell hardness ≥85HBW; coarse grain layer ≤2.5mm; exfoliation corrosion ≥EA level, with high comprehensive performance automotive rear floor side beam profile. Specifically includes the following steps:
[0183] S1. Ingredients: Prepare aluminum alloy raw materials according to the following weight ratio: Si: 0.67%, Fe: 0.18%, Cu: 0.13%, Mn: 0.35%, Mg: 0.57%, Cr: 0.20%, Zn: 0.01%, and the balance is Al; wherein the total content of Mn and Cr exceeds 0.5%;
[0184] S2. Melting and casting: the aluminum alloy raw material prepared in step S1 is placed in a smelting furnace for melting and casting to obtain cast rods. During melting and casting, the melting temperature is 740°C, the refining temperature is 735°C, the refining agent dosage is 2.2kg / TAl, and waste materials are not allowed to be added. When molten aluminum appears in the smelting furnace, the electromagnetic stirrer of the smelting furnace is turned on to make the molten alloy elements more evenly distributed. The refining agent is pumped into the surface of the molten aluminum by argon gas. After refining, the slag is removed by a slag removal vehicle. After slag removal, the molten aluminum is allowed to stand for 15 minutes before casting. In order to prevent cracks from occurring at the bottom of large-diameter cast rods during casting, pure aluminum chips are spread on the bottom of the crystallizer before casting and molten aluminum is placed into the crystallizer. Casting begins when the aluminum chips are in a semi-solidified state. The cast rods obtained using this technology have good surface quality and effectively control the occurrence of bottom cracks. At the beginning of casting, Al-Ti-B wire is added to the aluminum liquid for grain refinement. Al-Ti-B wire can be added to the aluminum liquid through wire feeding equipment. The casting temperature is 705℃, the casting speed is 29mm / min, and the cooling water flow rate is 2.2m 3 / min, during casting, the aluminum liquid is degassed by three graphite rotor degassing technology to reduce the hydrogen content in the aluminum liquid. The speed of each graphite rotor is controlled at 310r / min, the diameter of the cast rod is 582mm, and the slag content of the cast rod must meet the secondary requirements of GB / T32186-2015; the macrostructure of the cast rod is tested, and the macrograin structure of the cast rod meets the grain size level 1 and is qualified. The macrograin detection diagrams of the first and second parts of the cast rod are shown as follows Fig. 22 and Fig.23 As shown;
[0185] S3. Homogenization of cast rods: The cast rods obtained in step S2 are homogenized to obtain round ingots, which may be round ingots of Φ582 mm, and the homogenization temperature is 560 ° C, and the homogenization time is 6 h;
[0186] S4 extrusion: the round ingot obtained in step S3 is placed in an extrusion device for extrusion to obtain a profile, using a 12500 ton extruder for extrusion, the round ingot length is 1680mm, the round ingot car, the round ingot head heating temperature is 520 ° C, the tail heating temperature is 510 ° C, the extrusion die heating temperature is 500 ° C, the extrusion barrel heating temperature is 440 ° C, the product speed is 1m / min;
[0187] S5. Profile quenching, stretching and cutting: The profile obtained in step S4 is quenched by online water mist quenching, and after quenching, it is stretched online with a stretching amount of 1%, and the stretched profile is cut into a specified length;
[0188] S6. Aging treatment: The profile cut in step S5 is subjected to aging treatment at an aging temperature of 175° C. for an aging time of 8 h to obtain a rear floor side beam profile for an automobile.
[0189] Dimension accuracy at key positions: Three pieces are randomly selected from the produced rear floor side beam profiles for automobiles, numbered and measured. The results of the key position dimension detection are shown in Table 26.
[0190] Table 26 Key dimension test results
[0191]
[0192] Macrostructure: alkaline corrosive solution is used; test standard: GB / T6892-2015 General industrial aluminum and aluminum alloy extrusion profiles; test method: GB / T3246.2-2012 Deformed aluminum and aluminum alloy product structure inspection method Part 2: Macrostructure inspection method. Three pieces were randomly selected from the produced rear floor side beam profiles for automobiles and numbered and tested. The macrostructure test results are shown in Table 27. It can be seen that there are more coarse grains at the free end, and the profiles are found to have poor welding performance in the subsequent welding process.
[0193] Table 27 Low-power tissue detection results
[0194]
[0195]
[0196] High-magnification structure: Test equipment: AXIO universal research-grade inverted material microscope; Test standard: GB / T6892-2015 General industrial aluminum and aluminum alloy extrusion profiles; Test method: GB / T3246.1-2012 Deformed aluminum and aluminum alloy product structure inspection method Part 1: Microstructure inspection method. One piece was randomly selected from the produced rear floor side beam profiles for automobiles and numbered and inspected. The high-magnification metallographic structure inspection results are shown in Table 28. The high-magnification structure inspection diagram is shown in Table 28. Fig.24 shown.
[0197] Table 28 High magnification metallographic structure test results
[0198]
[0199] Mechanical properties and Brinell hardness: Testing equipment AG-X 100KN electronic universal testing machine, OMNITEST multifunctional hardness tester; Testing methods GB / T16865-2013 Specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products, GB / T231.1-2018 Brinell hardness test of metallic materials Part 1: Test method; Judgment criteria: tensile strength ≥250MPa, yield strength ≥200MPa, elongation after fracture A 50 mm≥6%, Brinell hardness≥85HBW. Three pieces were randomly selected from the produced rear floor side beam profiles for automobiles, numbered and tested. The mechanical properties test results are shown in Table 29. It can be seen that the mechanical properties have decreased.
[0200] Table 29 Mechanical properties test results
[0201]
[0202] Exfoliation corrosion: Test equipment: digital constant temperature water bath crucible; Test standard: GB / T22639-2008 Exfoliation corrosion test method for aluminum alloy processed products; 3 pieces were randomly selected from the produced rear floor side beam profiles for automobiles and numbered and tested. The exfoliation corrosion test results are shown in Table 30. Fig.25 As shown, the exfoliation corrosion results are poor.
[0203] Table 30 Exfoliation corrosion test results
[0204]
[0205]
[0206] Comparative Example 2: This comparative example provides a method for producing a rear floor side beam profile for automobiles, the purpose of which is to produce a rear floor side beam profile for automobiles with an outer circle of 471 mm, an outer contour size and an outer wall thickness of GB / T 14846-2008 ultra-high precision, wherein the cantilever right angle tolerance is ±0.5°, the opening size tolerance is 0-0.5 mm; the yield strength is ≥200 MPa, the tensile strength is ≥250 MPa, and the elongation after fracture is A 50 ≥6%; Brinell hardness ≥85HBW; coarse grain layer ≤2.5mm; exfoliation corrosion ≥EA level, with high comprehensive performance automotive rear floor side beam profile. Specifically includes the following steps:
[0207] S1. Ingredients: Prepare aluminum alloy raw materials according to the following weight ratio: Si: 0.67%, Fe: 0.18%, Cu: 0.13%, Mn: 0.10%, Mg: 0.57%, Cr: 0.10%, Zn: 0.01%, and the balance is Al; wherein the total content of Mn and Cr is less than 0.4%;
[0208] S2. Melting and casting: the aluminum alloy raw material prepared in step S1 is placed in a smelting furnace for melting and casting to obtain cast rods. During melting and casting, the melting temperature is 740°C, the refining temperature is 735°C, the refining agent dosage is 2.2kg / TAl, and waste materials are not allowed to be added. When molten aluminum appears in the smelting furnace, the electromagnetic stirrer of the smelting furnace is turned on to make the molten alloy elements more evenly distributed. The refining agent is pumped into the surface of the molten aluminum by argon gas. After refining, the slag is removed by a slag removal vehicle. After slag removal, the molten aluminum is allowed to stand for 15 minutes before casting. In order to prevent cracks from occurring at the bottom of large-diameter cast rods during casting, pure aluminum chips are spread on the bottom of the crystallizer before casting and molten aluminum is placed into the crystallizer. Casting begins when the aluminum chips are in a semi-solidified state. The cast rods obtained using this technology have good surface quality and effectively control the occurrence of bottom cracks. At the beginning of casting, Al-Ti-B wire is added to the aluminum liquid for grain refinement. Al-Ti-B wire can be added to the aluminum liquid through wire feeding equipment. The casting temperature is 705℃, the casting speed is 29mm / min, and the cooling water flow rate is 2.2m 3 / min, during casting, the aluminum liquid is degassed by three graphite rotor degassing technology to reduce the hydrogen content in the aluminum liquid. The speed of each graphite rotor is controlled at 310r / min, the diameter of the cast rod is 582mm, and the slag content of the cast rod must meet the secondary requirements of GB / T32186-2015; the macrostructure of the cast rod is tested, and the macrograin structure of the cast rod meets the grain size level 1 and is qualified. The macrograin detection diagrams of the first and second parts of the cast rod are shown as follows Fig.26 and Fig. 27 As shown;
[0209] S3. Homogenization of cast rods: The cast rods obtained in step S2 are homogenized to obtain round ingots, which may be round ingots of Φ582 mm, and the homogenization temperature is 560 ° C, and the homogenization time is 6 h;
[0210] S4 extrusion: the round ingot obtained in step S3 is placed in an extrusion device for extrusion to obtain a profile, using a 12500 ton extruder for extrusion, the round ingot length is 1680mm, the round ingot car, the round ingot head heating temperature is 520 ° C, the tail heating temperature is 510 ° C, the extrusion die heating temperature is 500 ° C, the extrusion barrel heating temperature is 440 ° C, the product speed is 1m / min;
[0211] S5. Profile quenching, stretching and cutting: The profile obtained in step S4 is quenched by online water mist quenching, and after quenching, it is stretched online with a stretching amount of 1%, and the stretched profile is cut into a specified length;
[0212] S6. Aging treatment: The profile cut in step S5 is subjected to aging treatment at an aging temperature of 175° C. for an aging time of 8 h to obtain a rear floor side beam profile for an automobile.
[0213] Dimension accuracy at key positions: Three pieces are randomly selected from the produced rear floor side beam profiles for automobiles, numbered and measured. The results of the key position dimension detection are shown in Table 31.
[0214] Table 31 Key dimension detection results
[0215]
[0216] Macrostructure: alkaline corrosive solution is used; test standard: GB / T6892-2015 General industrial aluminum and aluminum alloy extrusion profiles; test method: GB / T3246.2-2012 Deformed aluminum and aluminum alloy product structure inspection method Part 2: Macrostructure inspection method. Three pieces were randomly selected from the produced rear floor side beam profiles for automobiles and numbered and tested. The macrostructure test results are shown in Table 32. It can be seen that there are more coarse grains at the free end and the profile is unqualified.
[0217] Table 32 Low-power tissue test results
[0218]
[0219] High-magnification structure: Test equipment: AXIO universal research-grade inverted material microscope; Test standard: GB / T6892-2015 General industrial aluminum and aluminum alloy extrusion profiles; Test method: GB / T3246.1-2012 Deformed aluminum and aluminum alloy product structure inspection method Part 1: Microstructure inspection method. One piece was randomly selected from the produced rear floor side beam profile for automobiles and numbered and inspected. The high-magnification metallographic structure inspection results are shown in Table 33. The high-magnification structure inspection diagram is shown in Table 33. Fig.28 shown.
[0220] Table 33 High magnification metallographic structure test results
[0221]
[0222] Mechanical properties and Brinell hardness: Testing equipment AG-X 100KN electronic universal testing machine, OMNITEST multifunctional hardness tester; Testing methods GB / T16865-2013 Specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products, GB / T231.1-2018 Brinell hardness test of metallic materials Part 1: Test method; Judgment criteria: tensile strength ≥250MPa, yield strength ≥200MPa, elongation after fracture A 50 mm≥6%, Brinell hardness≥85HBW. Three pieces were randomly selected from the produced rear floor side beam profiles for automobiles, numbered and tested. The mechanical properties test results are shown in Table 34. The mechanical properties test results are poor.
[0223] Table 34 Mechanical properties test results
[0224]
[0225] Exfoliation corrosion: Test equipment: digital constant temperature water bath crucible; Test standard: GB / T22639-2008 Exfoliation corrosion test method for aluminum alloy processed products; 3 pieces were randomly selected from the produced rear floor side beam profiles for automobiles and numbered and tested. The exfoliation corrosion test results are shown in Table 35. Fig.29 As shown, the exfoliation corrosion results are poor.
[0226] Table 35 Exfoliation corrosion test results
[0227]
[0228] The embodiments of the present invention are given for the purpose of illustration and description, and are not intended to be exhaustive or to limit the invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.
Claims
1. A method for producing a rear floor side beam profile for an automobile, characterized in that: The steps include: S1. Ingredients: Prepare aluminum alloy raw materials according to the following weight ratios: Si: 0.65% to 0.70%, Fe: ≤0.25%, Cu: 0.11% to 0.16%, Mn: 0.25% to 0.30%, Mg: 0.55% to 0.60%, Zn: ≤0.10%, Cr: 0.15% to 0.20%, and the balance is Al; S2. Casting: The aluminum alloy raw material prepared in step S1 is placed in a smelting furnace for casting to obtain a cast rod; S3. Homogenization of cast rods: homogenizing the cast rods obtained in step S2 to obtain round ingots; S4. Extrusion: placing the round ingot obtained in step S3 into an extrusion device for extrusion to obtain a profile, wherein the diverter slots on both sides of the feed port of the upper die of the extrusion die are progressive sinking bridges, and the round ingot is heated by a stepwise heating method, the heating temperature of the head end of the round ingot is 510°C to 530°C, the heating temperature of the tail end is 490°C to 510°C, the temperature of the extrusion barrel is 420°C to 460°C, the heating temperature of the extrusion die is 490°C to 510°C, and the product speed is 0.7m / min to 1.2m / min; S5. Profile quenching, stretching and cutting: quenching the profile obtained in step S4, stretching it online after quenching, and cutting the stretched profile into a specified length; S6. Aging treatment: The profile cut in step S5 is subjected to aging treatment at an aging temperature of 170°C to 180°C for 8 hours to obtain a rear floor side beam profile for automobiles.
2. The method for producing a rear floor side beam profile for an automobile according to claim 1, characterized in that: In the step S1, the ingredients are Si: 0.65% to 0.70%, Fe: ≤0.17%, Cu: 0.12% to 0.14%, Mn: 0.27% to 0.30%, Mg: 0.55% to 0.58%, Zn: ≤0.01%, Cr: 0.15% to 0.17%, and the balance is Al.
3. The method for producing a rear floor side beam profile for an automobile according to claim 1, characterized in that: In the step S2, during the smelting and casting, the smelting temperature is 730°C to 750°C. When molten aluminum appears in the smelting furnace, the electromagnetic stirrer of the smelting furnace is turned on, and the refining agent is pumped into the surface of the molten aluminum by argon gas. After refining, the slag is removed by a slag removal vehicle. After the slag is removed, the molten aluminum is allowed to stand for 15 minutes before casting. Before casting, pure aluminum chips are spread on the bottom of the crystallizer and molten aluminum is placed into the crystallizer. When the aluminum chips are in a semi-solidified state, casting is started. At the beginning of casting, Al-Ti-B wire is added to the molten aluminum for grain refinement. The casting temperature is 695°C to 715°C, the casting speed is 29 mm / min, and the cooling water flow rate is 2.2 m 3 / min. During casting, the aluminum liquid is degassed by three graphite rotor degassing technology, and the speed of each graphite rotor is controlled at 310r / min.
4. The method for producing a rear floor side beam profile for an automobile according to claim 1, characterized in that: In the step S3, the temperature of the homogenization treatment is 560° C., and the time of the homogenization treatment is 6 hours.
5. The method for producing a rear floor side beam profile for an automobile according to claim 1, characterized in that: In the step S3, the round ingot is a Φ582 mm round ingot.
6. The method for producing a rear floor side beam profile for an automobile according to claim 1, characterized in that: In the step S4, the round ingot is subjected to a peeling treatment before extrusion, and the peeling treatment includes peeling by car skin or hot peeling by an online peeling machine. During extrusion, the ingot is extruded by a 12,500-ton extruder with an extrusion ratio of 30.
64.
7. The method for producing a rear floor side beam profile for an automobile according to claim 1, characterized in that: In the step S4, the progressive sinking bridge of the extrusion die includes a plurality of stepped diverter bridges, and each of the diverter bridges has a different depth and width.
8. The method for producing a rear floor side beam profile for an automobile according to claim 1, characterized in that: In the step S5, the quenching method is online water mist quenching.
9. The method for producing a rear floor side beam profile for an automobile according to claim 1, characterized in that: In the step S5, the stretching amount in the online stretching is 0.5% to 1.5%.
10. The method for producing a rear floor side beam profile for an automobile according to claim 1, characterized in that: In the step S6, the diameter of the circumscribed circle of the rear floor side beam profile for the automobile is 471 mm.